An Interpolated Model Recovery Anti-Windup for a Canard-Guided Projectile Subject to Uncertainties - Thai, Sovanna; Roos, Clement; Biannic, Jean-Marc; Theodoulis, Spilios (2021 European Control Conference (ECC), 2021)
This paper presents an autopilot design for a dual-spin guided projectile subject to aerodynamic uncertainties and actuator saturations. The proposed design consists of a gain-scheduled baseline controller together with an interpolated dynamic anti-windup compensator based on model recovery. Evaluation of the closed-loop is done through IQC-based analysis at an operating point, and through Monte Carlo simulations. Both assessments show that the addition of an anti-windup compensator can drastically improve the behaviour of the system in degraded flight conditions.